CUBE ONLINE ANALYTICAL MODEL (COLAM) IN THE RIVER SHIPPING LOGISTIC FORECASTING - Natalia Verbitskaya; Darko B. Vuković; Andrey Mehrentsev; Dejana Jakovljević; Aleksandra Vujko (Zbornik Radova: Geografski institut "Jovan Cvijić", 2018)
In this paper authors developed Cube Online Analytical Model (COLAM) which should anticipate various restrictions and hazards in river transport system. The aim is to construct a theoretical model which will predict certain delays in transport time caused by topographic and hydrographic constraints, natural hazards (such as ice, floods and droughts), economic and political constraints (tariff barriers between the countries, operating costs, terminal costs and sanctions, the threat of war, etc.) and different technical accidents. COLAM integrates hydroinformatic and hydrologic base of knowledge with real time and gives possibility to provide information for economic queries with different hierarchy of time. COLAM is methodological and practical instrument for this challenge. It integrates hydroinformatic and hydrologic base of knowledge with real time. The model in each concrete case is created to receive information about possible changing of navigation periods on the base of multi-dimension all of three groups of risks (natural hazards, social and technical hazards) as also their combinations.